Biochemical parameters in the blood of grass snakes (Natrix natrix) in ecosystems under varying degrees of anthropogenic influence - V. Y. Gasso; A. M. Hahut; S. V. Yermolenko (Regulatory Mechanisms in Biosystems, 2016)
The grass snake Natrix natrix (Linnaeus, 1758) is a partly hygrophilous species, distributed throughoutUkraine. This snake may be considered as a test object for environmental biomonitoring. Modern biochemical methods make it possible to obtain new scientific data on the effects of anthropogenic pressure on reptiles. Blood is a sensitive and informative indicator of the condition of an organism as it responds quickly to most changes in exogenous and endogenous factors, and reflects negative influences on both individual and, indirectly, populations. Changes in biochemical parameters may be used as biomarkers of the state of health of reptiles in ecosystems under varying degrees of anthropogenic pressure. Due the increase in anthropogenic influence the development and introduction of new methods of perceptual research, collection of up-to-date information and development of a database of reptile biochemical parameters have become an urgent priority. We collected mature individuals of the grass snake in floodplain ecosystems on the right bank of the Dnieper River in Dnipropetrovsk city. Grass snakes from floodplain habitats on the left bank of theSamaraRiver (O.L. Belgard Prysamarskii International Biosphere Station, Novomoskovsk district, Dnipropetrovsk province) were studied as the control specimens. Our study demonstrated statistically significant differences between snakes from the study sites in the amount of albumin, urea and urea nitrogen, and inorganic phosphorus, as well as in alanine aminotransferase (ALT) and alkaline phosphatise (AP) activity. The amount of albumin in the blood serum of specimens from the anthropogenically transformed areas was significantly lower (by 25%) than in that of the snakes caught in the control habitats. Decrease of the albumin concentration usually indicates abnormal processes in the kidneys and liver. According to the changes observed in the concentration of albumin, a corresponding increase in the albumin to globulin ratio by about 30% was found. A statistically significant increase in alkaline phosphatase activity may demonstrate negative physiological changes in tissues of the liver and bones. Increased activities of ALT and AP indicate certain changes in the physiological condition of the liver of snakes from the anthropogenically transformed site. Other studied parameters did not exceed the limits found for different species of reptiles. Significant differences between certain biochemical parameters in the serum of snakes from the studied regions may reflect pathological processes in the grass snakes from transformed ecosystems, mainly in their liver and kidneys. The results can be used in future studies as benchmarks for assessing the condition of the organism of this species in the conditions of anthropogenic stress.